Changes in natural forest land cover of the Eucalyptus urophylla type in the Mutis Timau area in 2002-2022, East Nusa Tenggara Province - Marimpan, Lusia Sulo; Purwanto, Ris Hadi; Wardhana, Wahyu; Idris, Fahmi; Sumardi, Sumardi (Brawijaya University, 2024)
Anthropogenic activities carried out by communities around forests in production forests, protected forests, and conservation forests have an impact on changes in the land cover of these areas. This impact is difficult to avoid because, on the other hand, production forests and protected forests are in direct contact with the lives of local communities. Changes in land cover have a significant impact on the contribution of Folu Net Sink, which is set by the government at 31.89% in 2030 with its efforts. This research aims to provide an overview of land cover changes that occurred in natural forests of the Eucalyptus urophylla type from 2002 to 2022. The method used in this research is a supervised/guided digital classification technique. Ground checks were also carried out in this research to match the accuracy of the image data with the actual conditions in the field. The research results show that changes in land cover in 2012 and 2017 were very extreme. Forest fires were the cause of changes in land cover during this period. Meanwhile, in 2002, 2007, and 2022, the land cover was still good, in a positive direction. The causes of changes in land cover are encroachment activities, encroachment, illegal logging, firewood theft, rice fields, forest fires, plantations, and farming. Forest preservation provides very high benefits for life on earth. Therefore, it is important to pay attention to the welfare of local communities so that they do not damage the forest, as well as increase the capacity to educate the community regarding zoning or blocks in conservation and protected forests. Apart from that, good forest management is needed to ensure forest sustainability in the future.